On the 'Holy Poor': from the Hebrew Bible to the literature of developing countries, 1945 - - David Aberbach (London School of Economics and Political Science (LSE), Department of International Development, 2017)
The notion of the 'holy poor' ceased to figure significantly in the literature of most developed countries after World War II but continues to resonate in countries where poverty is widespread and the Church has grown. This paper explores 1. the origins of the 'holy poor' in the Hebrew Bible, and its consequent betrayals and survivals; 2. the discrepancy between the image of the poor in English Poor Law and English literature from Shakespeare to Orwell; and 3. the continuing relevance of Scripture to literature on the poor in post-1945 developing countries, in Nigeria (Achebe), South Africa (Coetzee), Egypt (Mahfouz), and Brazil (Lispector).
Keywords: 330; Poverty; English Poor Law; Nigeria; South Africa; Egypt; Brazil